Application of progressive exercise training based on mMRC grading in respiratory rehabilitation for patients with chronic obstructive pulmonary disease in a primary healthcare setting - Tingting GE; Chengyue ZHU; Yanan ZHANG; Zixuan ZHENG; Jiannan LI; Junqing LI; Zhijun JIE; Jindong SHI; Hanwei ZHAO (Zhongguo Linchuang Yixue)
ObjectiveTo explore the efficacy of progressive exercise training based on the modified Medical Research Council dyspnea scale (mMRC) grading in respiratory rehabilitation for patients with chronic obstructive pulmonary disease (COPD) at a primary healthcare setting. MethodsA total of 106 patients with COPD admitted to Zhuanqiao Community Health Service Center in Shanghai from Aug.1, 2022 to Jul. 30, 2024 were selected as research subjects. They were randomly divided into a study group and a control group in a 1∶1 ratio, with 53 patients in each group. The control group received conventional treatment, while the study group received conventional treatment combined with progressive exercise training. After 4 weeks of continuous treatment, the changes in the 6-minute walk test (6MWT), COPD assessment test (CAT) score, mMRC grading, Global Initiative for Chronic Obstructive Lung Disease (GOLD) grading and pulmonary function were compared between the two groups. ResultsPatients in both groups showed improvements in 6MWT distance, CAT score, mMRC grading, GOLD grading, and pulmonary function compared to baseline (P＜0.05). Moreover, the study group had better improvements in 6MWT distance, CAT score, mMRC grading, GOLD grading, and pulmonary function than the control group (P＜0.05). ConclusionsConventional treatment combined with progressive exercise training based on mMRC grading can enhance the effect of respiratory rehabilitation in patients with COPD, particularly in improving pulmonary function and exercise tolerance.